2021
DOI: 10.1007/s00170-021-06778-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of geometrical accuracy of active devices for 3D orthopaedic reconstructions

Abstract: The use of 3D digitizing tools is becoming the base for subject-specific products, such as the orthopaedic production process of orthoses and prostheses. This paper aims at comparing the metrological behaviour of low-cost devices (Kinect 1 and 2 by Microsoft, Structure Sensor by Occipital) and high-resolution active sensors (O&P Scan by Rodin4D, NextEngine Ultra HD, Konica Minolta Vivid 9i, GOM ATOS II 400 and Artec Leo) for the survey of human body parts. A calibrated flat plane and a test-field composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Redaelli et al 17 compared 3 low-cost devices (SS I, Kinect 1, and Kinect 2) against a high-resolution laser scanner (GOM ATOS II 400) for the fabrication of orthotic devices by scanning the hand, thigh, and chest regions of a mannequin. Among these low-cost devices, SS I was found to have acceptable accuracy with mesh sizes of 0.6 mm, 1.2 mm, and 1.6 mm for the hand, thigh, and chest, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Redaelli et al 17 compared 3 low-cost devices (SS I, Kinect 1, and Kinect 2) against a high-resolution laser scanner (GOM ATOS II 400) for the fabrication of orthotic devices by scanning the hand, thigh, and chest regions of a mannequin. Among these low-cost devices, SS I was found to have acceptable accuracy with mesh sizes of 0.6 mm, 1.2 mm, and 1.6 mm for the hand, thigh, and chest, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among these low-cost devices, SS I was found to have acceptable accuracy with mesh sizes of 0.6 mm, 1.2 mm, and 1.6 mm for the hand, thigh, and chest, respectively. 17 Zahia et al 18 compared the SS I and Go!Scan 20 to scan the abdomen and identified SS I to be superior for speed, ease of use, and size obstruction. However, although these studies compared the performance measures of different 3D scanners, none have assessed 3D scanning of the foot and ankle regions for the fabrication of AFOs.…”
Section: Introductionmentioning
confidence: 99%
“…Structured light scanners are handheld and portable, and provide real-time scanning, whereas laser scanners can be static with a set measurement volume, such as the one in the study mentioned previously [26]. Davide et al investigated the difference between high-and low-cost scanning equipment; this highlighted that whilst high and low cost fixed scanners may have increased accuracy, the set up and scan time would limit their applications in prosthetics when compared to hand held devices for direct limb scanning [28]. Smartphone photogrammetry can be considered handheld as it uses a mobile device with no fixed measurement volume; currently, however, there are no real-time scanning options available on common smartphones suitable for prosthetic applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of 3D scanning technology, it is possible to use 3D scanners to scan the shape of the foot [20,[27][28][29][30][31]. Three major types of 3D scanning methods have been developed and used for body shape reconstruction, namely laser sensors [27,28,30], depth sensors [31,32], and photogrammetry [20,29,33].…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of 3D scanning technology, it is possible to use 3D scanners to scan the shape of the foot [20,[27][28][29][30][31]. Three major types of 3D scanning methods have been developed and used for body shape reconstruction, namely laser sensors [27,28,30], depth sensors [31,32], and photogrammetry [20,29,33]. However, for the measurement of the foot, a major limitation of the existing 3D scanning methods is that it only works during non-weight-bearing conditions because the sole of the foot cannot be measured when it is in contact with the floor under weight-bearing conditions.…”
Section: Introductionmentioning
confidence: 99%